2014
DOI: 10.1371/journal.pone.0101046
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Species Traits for Species Distribution on Oceanic Islands

Abstract: Understanding species' ability to colonize new habitats is a key knowledge allowing us to predict species' survival in the changing landscapes. However, most studies exploring this topic observe distribution of species in landscapes which are under strong human influence being fragmented only recently and ignore the fact that the species distribution in these landscapes is far from equilibrium. Oceanic islands seem more appropriate systems for studying the relationship between species traits and its distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…B). In contrast, Vazačová and Münzbergová () found that certain species were better dispersed by wind to the youngest and westernmost island of the Canaries (El Hierro), although they found no relationship between dispersal traits and overall species distribution across the Canary Islands. Further research confirming the poor dispersal ability of anemochorous plants and disentangling the causes behind their limited distribution is necessary.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…B). In contrast, Vazačová and Münzbergová () found that certain species were better dispersed by wind to the youngest and westernmost island of the Canaries (El Hierro), although they found no relationship between dispersal traits and overall species distribution across the Canary Islands. Further research confirming the poor dispersal ability of anemochorous plants and disentangling the causes behind their limited distribution is necessary.…”
Section: Discussionmentioning
confidence: 97%
“…These results are consistent with a recent meta‐analysis in which fleshy fruits appear to have been related with wide inter‐island distributions in several oceanic archipelagos (García‐Verdugo et al ). In comparison, the role of epizoochorous syndromes in favouring island colonization has been addressed less frequently (Sorensen , Aoyama et al , Vazačová and Münzbergová ). Nevertheless, it has been shown that species without any specialization toward animal dispersal can also be effectively transported by them; this phenomenon is considered a non‐standard mean of dispersal (Higgins et al , Nogales et al , Heleno et al , b).…”
Section: Discussionmentioning
confidence: 99%
“…Most orchids seeds are comparable in size to the diaspores of ferns, mosses, liverworts and fungi (lichens), groups that have been found to have distribution patterns that can be explained by prevailing wind connectivity (Muñoz et al, ; Sanmartín et al, ). Therefore, within the two groups of anemochorous and thalassochorous species, future studies are needed to list and to rank species by the efficiency of diaspore syndromes based on experimentation, as done for some species from the floras of the Canaries (Vazacová & Münzbergová, ) and Azores (Esteves, Costa, Vargas, Freitas, & Heleno, ).…”
Section: Discussionmentioning
confidence: 99%
“…). Additionally, Aeonium species produce relative small (0.4–0.6 mm long) and light (0.02–0.04 mg) seeds, suggesting some suitability for wind dispersal (Liu ; Vazačová and Münzbergová ). Pollination by insects and wind dispersal of seeds might facilitate common exchange of alleles and genotypes between nearby populations.…”
Section: Methodsmentioning
confidence: 99%
“…Pollination by insects and wind dispersal of seeds might facilitate common exchange of alleles and genotypes between nearby populations. However, specialized seed traits that would advance anemochory or other potential long‐distance dispersal are lacking, and dispersal capabilities of Aeonium species have been shown only moderate (Vazačová and Münzbergová ). Thus, gravity is probably the most important dispersal agent besides more or less occasional wind drift events.…”
Section: Methodsmentioning
confidence: 99%